PERCERAIAN DI MASA PANDEMI COVID-19; ANALISIS TERHADAP PENYEBAB MENINGKATNYA ANGKA PERCERAIAN DI SEMARANG - Wifa Lutfiani Tsani; Alfian Daha Wira Utama (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
Every couple who agrees to marry hopes to build a family that is sakinah, mawaddah, and warahmah which is full of grace and harmony in married life. However, a number of marriages must end in divorce. During the Covid-19 pandemic, a spike in the divorce rate was found at the Semarang Religious Court. The data states that more divorces are caused by financial problems that spread into domestic disputes that end in separation. Another factor that recorded the high number of divorces during the pandemic was the increasing intensity of husband and wife meetings which resulted in household conflicts. In addition, the wife's awareness of the unequal fulfillment of rights and obligations, especially the hampered husband's livelihood, has resulted in the wife suing for divorce in the Religious Courts. This economic issue is inseparable from the conditions of the PSBB and PPKM during the Covid-19 pandemic.